2007
DOI: 10.1016/j.jmb.2006.11.097
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the 5 S rRNA-binding Ribosomal Proteins for Cell Viability and Translation in Escherichia coli

Abstract: SummaryA specific complex of 5 S rRNA and several ribosomal proteins is an integral part of ribosomes in all living organisms. Here we studied the importance of Escherichia coli genes rplE, rplR and rplY, encoding 5 S rRNA-binding ribosomal proteins L5, L18 and L25, respectively, for cell growth, viability and translation. Using recombineering to create gene replacements in the E. coli chromosome, it was shown that rplE and rplR are essential for cell viability, whereas cells deleted for rplY are viable, but g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…Recombineering is a novel technique of manipulating the DNA sequences in bacterial cells using the Red recombination functions of phage (4). It has been shown to be very efficient in generating gene knockouts in E. coli (2,16,45). Recombineering was carried out according to the methods described by Thomason et al (39) with some modifications.…”
Section: Methodsmentioning
confidence: 99%
“…Recombineering is a novel technique of manipulating the DNA sequences in bacterial cells using the Red recombination functions of phage (4). It has been shown to be very efficient in generating gene knockouts in E. coli (2,16,45). Recombineering was carried out according to the methods described by Thomason et al (39) with some modifications.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that during the folding of 23S rRNA, these proteins initiate the formation of two main and independent assembly centers (161a). Proteins L5, L18, and L25 mediate the principal interactions between the 5S and 23S rRNA and are necessary for the correct formation of the central protuberance (112).…”
Section: Assembly Of Ribosomal Subunits (I) Assembly Of the 30smentioning
confidence: 99%
“…Bacterial 5S RNA interacts directly with three ribosomal proteins (r-proteins)-L18, L25, and L5 (Chen-Schmeisser and Garret 1977), two of which, L5 and L18, are essential for viability (Korepanov et al 2007). Although the rplY gene encoding L25 is not absolutely required for survival, Escherichia coli cells deficient in L25 reveal a slow growth phenotype even in rich media under normal growth conditions, indicating importance of L25 for ribosome functioning (Korepanov et al 2007). As shown recently (Korepanov et al 2012), L5 plays a crucial role in the CP formation during assembly of the 50S subunit, but precise roles for L18 and L25 still remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%